Advertising and Competitive Behaviour of Selected Australian Firms - Metwally, M. M. (The Review of Economics and Statistics, 1975)
IN spite of the interest in advertising, research in the field has not been very impressive. The reason for this is simply that problems presented in marketing and advertising are often unique, and their satisfactory solutions require the development and synthesis of their own body of theory. This body is lacking.1 In Australia, in particular, advertising has not attracted a large amount of research. This is mainly because of the slowness with which marketing has been accepted as a separate subject of study in our universities, the lack of official statistical information on advertising, and the reluctance of Australian companies to disclose information on their marketing promotion efforts and expenses. The aim of this study is to analyse the marketing competitive behaviour of eight consumer goods producers, which economists and marketing analysts claim to be advertising heavily in Australia (Metwally, 1973a). In particular we estimate the magnitude of advertising expenditure consistent with the object of profit maximisation, and compare it with the actual expenditure of some dominant firms producing those commodities. In section I, we develop a mathematical model of demand similar to that of Dorfman and Steiner (1961). Section II considers the form of functional relationship that exists between sales, price and advertising. In section III different econometric models of competitive interdependence are compared and evaluated. Finally in section IV, the findings and their main implications on promotional competition are discussed. I